Risk assessment of large crude oil depot based on interpretative structural model and system dynamics. (30th April 2020) - Chen, Li-Qiong; Feng, Yu-Xiang; Zhen, Hong-Long; Li, Qiao-Chu; Lu, Jing-Yang
In this paper, the interpretative structural model is used to determine the causality among the risk factors and a system dynamics model is established. The method is applied to the risk analysis of a large crude oil depot. The results show that the safety atmosphere and supervision play critical roles on the risk of the oil depot. At the mature stage of risk development, improvements in the equipment risk and management risk has the greatest impact on the overall risk. The degree of education, equipment usage time, safety atmosphere and supervision are the key risk factors for the human, equipment, environmental and management risk subsystems, respectively. This result provides a scientific basis to understand the trend of risk dynamic, risk evolution mechanism and fundamental risk factors and fundamentally prevent the occurrence of large crude oil depots. [Received: March 16, 2018; Accepted: December 17, 2018]